Words of wisdom : intro to philosophy - Ondich, Jody; BC Open Textbook Project; BCcampus ([Jody Ondich], 2018)
"Words of wisdom can come from anyone. In this text, we discuss topics ranging from "Are humans good by nature?" to "Is there a God?" to "Do I have the right to my own opinion?" Philosophy is the study of wisdom and can emerge in our conversations in places like social media, school, the family dinner table, and even the car. This text uses materials that are 2,500 years old and materials that were in the news recently. Wise people come in all shapes and types, and from every culture on earth. Poetry and folktales, sacred writings and letters, dialogues and interviews, news columns, podcasts, TED Talks, YouTube videos, and even comedy are all part of the content in this text"--BCcampus website.
Classics -- Medieval Materials -- Spiritual Philosophy and Tales from the World -- Early Modern Wisdom 1500-1750 -- Late Modern Wisdom 1750-1950 CE -- Modern Wisdom -- Links to Additional Great Resources.
Includes bibliographical references.
Mode of access: World Wide Web.
This bibliographic record is available under the Creative Commons CC0 "No Rights Reserved" license.
Online version, 2018; title from PDF (viewed on July 18, 2018).
Keywords: Philosophy; Wisdom; Electronic books